2017
DOI: 10.1186/s13098-017-0207-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of diabetes in a large community-based study in North India: results from a STEPS survey in Punjab, India

Abstract: AimsIndia is the diabetes capital with home to 69.1 million people with DM, the second highest number of cases after China. Recent epidemiological evidence indicates a rising DM epidemic across all classes, both affluent and the poor in India. This article reports on the prevalence of diabetes and pre-diabetes in the North Indian state of Punjab as part of a large household NCD Risk Factor Survey.MethodsA household NCD STEPS survey was done in the state of Punjab, India in a multistage stratified sample of 512… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
131
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(163 citation statements)
references
References 21 publications
25
131
7
Order By: Relevance
“…Our study adds to the limited but growing body of evidence suggesting that diabetes is no longer confined to urban areas of India and is a matter of concern in rural areas as well. 16 In our study increase in age, alcohol intake, family history of diabetes, stress, overweight/obesity and hypertension were found to be associated with diabetes. Many studies have also found a positive association with family history, hypertension and overweight with Diabetes.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Our study adds to the limited but growing body of evidence suggesting that diabetes is no longer confined to urban areas of India and is a matter of concern in rural areas as well. 16 In our study increase in age, alcohol intake, family history of diabetes, stress, overweight/obesity and hypertension were found to be associated with diabetes. Many studies have also found a positive association with family history, hypertension and overweight with Diabetes.…”
Section: Discussionsupporting
confidence: 48%
“…Many studies have also found a positive association with family history, hypertension and overweight with Diabetes. [14][15][16][17][18] More than one third of the people were found to have random blood sugar more than 140 mg/dl indicating high proportion of population at risk of developing diabetes in future if preventive measures including life style modification are not followed.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the study conducted by Jaya Prasad Tripathy et al, which showed that the prevalence of diabetes is higher among the individuals belonging to the age group ranging from 45 to 69 years. 10 The study showed that the males had a higher incidence of diabetes (54%) than the females (46%). This is consistent with the study conducted by R.M.…”
Section: Discussionmentioning
confidence: 95%
“…India will be home to 69.1million people with DM, the second highest number of cases after China and will be aptly described as the capital city of Diabetes. 11,12 This situation mostly encourages the patients to seek alternative therapy mostly in addition to conventional medicines influenced by their socio-cultural beliefs.…”
Section: Discussionmentioning
confidence: 99%